2018
DOI: 10.1037/ebs0000104
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary perspective on orgasm.

Abstract: The capacity to experience an orgasm evolved to promote high-frequency sex in species with low reproductive rates. Growing evidence shows that orgasms also have a variety of other reproductive consequences. Based on a distinction between orgasm frequency and orgasm intensity, there is emerging evidence in humans that orgasms function to promote and fine tune what are often very different, sex-specific reproductive outcomes. We provide an overview of the effect of hormonal contraceptives on orgasm, mate choice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
3
11
0
2
Order By: Relevance
“…Women did not. Differences in various parameters of extrapair orgasmic experiences (latency to orgasm, frequency of orgasm, intensity of orgasm, and orgasm duration) were consistent with a priori predictions based on sex differences in fitness maximization (Gallup, Burch, & Petricone, 2012;Gallup, Towne, & Stolz, 2018).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Women did not. Differences in various parameters of extrapair orgasmic experiences (latency to orgasm, frequency of orgasm, intensity of orgasm, and orgasm duration) were consistent with a priori predictions based on sex differences in fitness maximization (Gallup, Burch, & Petricone, 2012;Gallup, Towne, & Stolz, 2018).…”
supporting
confidence: 77%
“…At one extreme, orgasms can be brief and perfunctory, at the other, they can be lasting, intense, and inordinately gratifying. Gallup et al (2018) contend that all of these dimensions of orgasm evolved to promote specific reproductive outcomes. Gallup et al (2012) were the first to propose that variation in orgasm intensity for men is a proxy for sperm recruitment, and they refer to this as the Topping-Off Hypothesis.…”
Section: Orgasmmentioning
confidence: 99%
“…Unfortunately, the authors erroneously thought that this tenting reflex would facilitate sperm transport when it actually does the exact opposite, by delaying it! In fact, they are not the only authors (Gallup et al, 2018: King et al, 2016 who still question or ignore that vaginal tenting occurs when a woman becomes sexually excited and that this will delay the transport of spermatozoa until the arousal subsides. This rejection occurs despite a number of published studies that have incontestably confirmed the occurrence of vaginal tenting using direct observation and filming, genital imaging, and electrical recording (see Levin, 2011aLevin, , 2017b for the references).…”
Section: The Confusion As To What Female Genital Structures Are Stimulated During Coitusmentioning
confidence: 99%
“…Further challenges to the Sire Choice Hypothesis include data from Sherlock et al (2016) which found support for partner attractiveness increasing orgasm, but not masculinity, dominance, or fitness as found in previous studies. Gallup et al (2018) offer alternative explanations for absent but expected effects according to Sire Choice, suggesting that the methodology used may have limited partner fitness in the sample, since women were asked to report on their current partner and one with which they had the most orgasms. Still, it is fairly common for existing research on women's orgasm to ask women to reflect on a current or past partner, so similar criticisms could be lodged against those studies as well.…”
Section: Sire Choicementioning
confidence: 99%